Rubber seed and oil - Azeemoddin G; Thirumala Rao S D
A study was conducted on availability of rubber seeds and the characteristics and composition of rubber seeds and fresh harvested seeds were analysed. The area under rubber plantation by the close of 1960 was over 3 lakh acres. The annual availability of seeds was estimated to be 30,000 tons on the basis of an assumed seed production of 1 ton per 10 acres. The average cost was worked out as 1,300 perton of rubber seed. The peak seed fall season is from July to August. The average weight of fresh rubber seed is 4gm on a moisture free basis. The average shell and kernel contents are 41.7 percent and 58.3 percent respectively. Moisture distribution in the whole seed is predominantly in the kernel. Oil content of kernel on an average was 42 percent. The oil characteristics from extraction of predried kernels with light petroleum ether was yellow to brown with a mean iodine value of 136.0. Rubber seed oil is used for both edible& industrial purposes. In the context of the non-utilisation of rubber seeds in India for oil processing, the study highlighted the potential for rubber seed processing in the country.
Keywords: Chemical composition; India; Rubber seed oil; Rubber seed oil; Seed utilisation